Drying characteristics of palm kernel cake in a radial flow packed bed - Pang, Hooi Kim; Sivakumar Kumaresan; Chu, Chi Ming (Asian Network for Scientific Information, 2014)
The drying characteristics of Palm Kernel Cake (PKC) were investigated in a radial flow packed bed to understand the transfer processes in Solid State Fermentation (SSF). The 1.50 mm Palm Kernel Cake (PKC) particles with an initial moisture content of 50% on dry basis (d.b) was the filler material. The drying experiments were conducted using heated ambient air for four air temperatures (35, 45, 55 and 65°C) and three air flows (65.33, 75.33 and 92.33 LPM) in a laboratory radial flow packed bed. The drying data were then fitted to the different semi-theoretical models such as Lewis, Page, modified Page, logarithmic and Henderson and Pabis based on the ratio of the difference between the initial, final moisture content and the equilibrium moisture content. The models were evaluated by comparing the determination coefficient (R2) and Root Mean Square Error (RMSE) through non linear regression analysis. The drying air temperature was found to be the dominant factor affecting the drying kinetics of PKC.